Kajian Pemanfaatan Hutan Kemasyarakatan Wolobobo (Studi Kasus Pada KTH Anugerah, KTH Sedang Mekar dan KTH Setia Kawan) sebagai Sumber Pendapatan di Desa Bela Kecamatan Bajawa Kabupaten Ngada Provinsi Nusa Tenggara Timur - Petrus Laga Rado; Maria M. E. Purnama; Astin E. Mau (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
The purpose of the study was to find out the forms of community forest utilization in the Wolobobo HKm by farming communities in KTH Anugerah, KTH Medium Mekar and KTH Setia Kawan. Knowing the amount of income generated by farming communities in KTH Anugerah, KTH Sedang Mekar and KTH Setia Kawan. Knowing the level of profit from the use of HKm for farming communities in KTH Anugerah, KTH Sedang Mekar and KTH Setia Kawan. This research was carried out in HKm Wolobobo, Ngada Regency which consisted of 32 KTH with KTH samples taken as much as 10% (3 KTH) of the total KTH. Determination of KTH sample is done by simple random sampling. Data collection techniques used in this study are primary data and secondary data. From the data collected, descriptive quantitative data analysis was carried out. The results showed that the form of utilization of Wolobobo Hkm Coffee and Ginger became the main commodities. Farming business in HKm Wolobobo provides relative benefits to farmers with the results after analyzing the R/C ratio of KTH Anugerah of 2.88, KTH Sedang Mekar of 4.93 and KTH Setia Kawan of 7.70 which is greater than 1, then the business This farmer is declared to be profitable.